Guidance for project development —GODP —applied to project practice in fashion design (ModaPalavra e-periódico, 2020)
The designer's design practice is associated with thedevelopment of a collection, which goes through severalstages until its materialization and availability in the market.Thus, in order tocoordinate its creation, it is important toapply a methodology that helps and systematizes the entireprocess of developing the clothing product. In this way, thisarticle aims to apply the Guidance Guide for theDevelopment of Projects (GODP), in the design practice ofFashion Design. For that, the applied, qualitative descriptiveresearch was used, through a bibliographical research.Initially, studies were carried out on the garment collectiondevelopment process and following these procedures wereapplied in the GODP methodology. The results show that theGODP applied to the design practice of fashion design canhelp the designers to understand the real needs of the usersand to manage the operational process of the collection ofclothing. However, using a user-centered methodology in thefashion design practice allows the collection of informationrelevant to the project, as well as raising data about thetarget audience, which favors the comfort, safety andusability of clothing
Keywords: fashion design; user-centered design; product development of clothing